(untitled) (Journal of the Bangladesh Agricultural University, 2025)
BAU Chia-1, registered in 2019 in Bangladesh for countrywide cultivation, is considered a superfood due to its high amount of ω-3 fatty acids. A field experiment was conducted from November 2024 to February 2025 to evaluate the effect of different seed rates on the growth, reproductive traits, and yield performance. Four seed rate treatments (T1 = 200 g ha-1, T2 = 250 g ha-1, T3 = 300 g ha-1, and T4 = 350 g ha-1) were assessed with three replications and a Randomized Complete Block Design (RCBD). T3 produced the tallest plant (145.067 cm), the highest fresh weight (28.67 g), and dry weight (8.1 g). The efficiency of photosynthetically active radiation and the number of leaves per plant were highest in the T4 treatment. On the other hand, canopy spread (44.67 cm) and inflorescence number plant-1 (8) were highest in T1. However, spikelet spike-1 was almost similar (7) in T1 and T2 seed rates. Despite that, the highest seed yield (1116.67 kg ha-1) was recorded in T2, followed by T3 (1083 kg ha-1), T4(933 kg ha-1), and T1(883 kg ha-1). In contrast, a lower population may be influenced by a lower seed rate in T1, whereas reduced growth and yield parameters from higher seed rates (T4) may be associated with increased intraspecific competition. Taken all together, the seed rate of 250 g ha-1, designated as T2, showed the most effective crop performance and productivity at the BAU research field in Mymensingh. However, further multi-location trials are required to validate these findings before making any recommendations. J Bangladesh Agril Univ 23(3): 304–310, 2025